PENGARUH PENGGUNAAN MODEL STAD TERHADAP AKTIVITAS DAN HASIL BELAJAR SISWA - Wahid Priyono; Pramudiyanti Pramudiyanti; Rini Rita T. Marpaung (Universitas Lampung, 2014)
This research aims to know the effect of STAD model towards learning achievement and student’s cooperative activity. The design of this research was pretest-posttest with non-equivalent. The subject of this research were students in the class VIIIB and VIIID, chosen by using purposive sampling. This research used quantitatif and qualitatif data. The quantitative data was obtained from cognitive achievement and analyzed statistic by U-test. The qualitative data was the description of student’s cooperative activities. The result showed that STAD model improves student’s achievement in experiment class by average gained about 0.58. The average gain of achievement in cognitive indicator C1 (0.81) and C2 (0.44). The activity of student’s cooperative in all observed aspects had moderate level that was 67.18 %. Therefore, the use of STAD learning model influences significantly towards the students’s learning achievement and improves the student’s cooperative activities on the subject of human digestive system.Penelitian ini bertujuan untuk mengetahui pengaruh model STAD terhadap hasil belajar dan aktivitas kerjasama siswa. Desain yang digunakan yaitu pretes postes non ekuivalen. Subjek penelitian siswa kelas VIIIB dan VIIID dipilih secara purposive sampling. Data penelitian berupa data kuantitatif dan kualitatif. Data kuantitatif berupa hasil belajar dan dianalisis secara statistik melalui uji-U. Data kualitatif berupa deskripsi aktivitas kerjasama. Hasil menunjukkan bahwa penggunaan model STAD meningkatkan hasil belajar siswa pada kelas eksperimen dengan rata-rata Gain 0,58. Rata-rata Gain C1 (0,81) dan C2 (0,44). Aktivitas kerjasama siswa dari semua aspek yang diamati berkriteria cukup yaitu 67,18 %. Dengan demikian, penggunaan model STAD berpengaruh signifikan terhadap hasil belajar siswa dan meningkatkan aktivitas kerjasama siswa pada materi pokok sistem pencernaan manusia. Kata kunci : aktivitas kerjasama, hasil belajar, model STAD